2021
DOI: 10.20473/jbk.v10i1.2021.35-44
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Pregnancy Intension Risk Factors in Indonesia With Demographic Health Survey (Dhs) in 2017

Abstract: The pregnancy intention can be divided into two, namely the desired pregnancy and unwanted pregnancy/Kehamilan Tidak Diinginkan (KTD). Unwanted pregnancy can cause negative impacts on the mother, such as not carrying out antenatal care (ANC) and abortion. Besides, babies born from KTD are more at risk of experiencing low birth weight and not getting breast milk/Air Susu Ibu (ASI) from their mothers. Therefore, the risk factors of pregnancy intention need to be known to prevent the incidence of KTD in Indonesia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
0
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
2
0
1
2
Order By: Relevance
“…Women aged more than 35 years are more likely to experience unintended pregnancies compared to those aged 35 or below. This aligns with previous research using DHS (Luthfina, 2021) and PPAS data (Sihite and Simbolon, 2023), indicating that mothers aged 35 and below have a lower tendency to experience unintended pregnancies compared to those above the age of 35. Smilarly, studies in India have shown a higher prevalence of unintended pregnancies in women aged more than 35 (Dutta, Shekhar and Prashad, 2015).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Women aged more than 35 years are more likely to experience unintended pregnancies compared to those aged 35 or below. This aligns with previous research using DHS (Luthfina, 2021) and PPAS data (Sihite and Simbolon, 2023), indicating that mothers aged 35 and below have a lower tendency to experience unintended pregnancies compared to those above the age of 35. Smilarly, studies in India have shown a higher prevalence of unintended pregnancies in women aged more than 35 (Dutta, Shekhar and Prashad, 2015).…”
Section: Resultssupporting
confidence: 91%
“…This tends to be ironic considering that contraceptive use is a step towards family planning. However the same result had been found in DHS analysis in Indonesia where contraceptive use has a significant relationship with unintended pregnancy (Luthfina, 2021). This result also aligns with research in Australia, indicating that women using contraception, especially oral contraceptives, have a higher tendency for unintended pregnancies.…”
Section: Resultssupporting
confidence: 86%
“…While this is not in line with research conducted by Dewi et al, which stated that there was a relationship between multiple pregnancies and premature rupture of membranes with a p-value of 0.01 (p<α=0.05) [32]. A healthy reproductive age range with a long lifetime is 20 to 35 [33]. Women over the age of 35 have a greater risk of fetal death and serious complications for the mother, which are more pronounced in mothers over 40 years of age [34].…”
contrasting
confidence: 58%
“…Hasil analisis pada tabel 1 dapat diketahui bahwa distribusi frekuensi berdasarkan status pekerjaan, lebih banyak wanita hamil di Indonesia tahun 2017 yang tidak bekerja (59,9%) dibandingkan dengan yang bekerja (40,1% pada wanita yang bekerja. (10)(11)(12) (13) Temuan ini juga didukung oleh Luthfina (2021) yang menemukan bahwa tidak ada hubungan status pekerjaan wanita dengan kehamilan tidak diinginkan. Hal tersebut dapat terjadi karena wanita yang sedang hamil memiliki perlindungan hukum di tempat kerjanya.…”
Section: Hasilunclassified
“…Hal tersebut dapat terjadi karena wanita yang sedang hamil memiliki perlindungan hukum di tempat kerjanya. (13) Pasal 82 ayat 2 pada UU No.…”
Section: Hasilunclassified